2019
DOI: 10.1021/acs.orglett.9b03587
|View full text |Cite
|
Sign up to set email alerts
|

Selectfluor-Mediated Stereoselective [1 + 1 + 4 + 4] Dimerization of Styrylnaphthols

Abstract: Stereoselective [1 + 1 + 4 + 4] dimerization of 1-styrylnaphthols has been developed by using Selectfluor as the oxidant for the first time. The reaction was compatible with various functional groups, giving a class of ethanodinaphtho­[b,f]­[1,5]­dioxocines with novel 3D skeletons. DFT calculations indicate that this method merges an intriguing stereoselective intermolecular 1 + 1 radical coupling to construct a bridged C–C bond and then an intramolecular [4 + 4] formal cycloaddition of the in situ generated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…Phenyl rings with either electron-withdrawing or electron-donating groups at the para position were compatible to our reaction conditions (5b-5e). As observed by Zhou and Chen et al, 18 a lower yield was nevertheless obtained with a strong electronwithdrawing substituent (5b). Notably, ortho-substituted phenyl rings were well tolerated furnishing the corresponding homodimer in up to 58% yield (5g and 5h, 5l and 5m).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Phenyl rings with either electron-withdrawing or electron-donating groups at the para position were compatible to our reaction conditions (5b-5e). As observed by Zhou and Chen et al, 18 a lower yield was nevertheless obtained with a strong electronwithdrawing substituent (5b). Notably, ortho-substituted phenyl rings were well tolerated furnishing the corresponding homodimer in up to 58% yield (5g and 5h, 5l and 5m).…”
Section: Resultssupporting
confidence: 66%
“…17 Recently, Zhou and Chen et al reported an efficient synthesis of these complex products 5 through a copper-catalyzed oxidative (1 + 1 + 4 + 4) dimerization of 1-styrylnaphthols using a stoichiometric amount of Selectfluor as the terminal oxidant. 18 To our knowledge, such photoinduced aerobic oxidative (1 + 1 + 4 + 4) homodimerization of 1-styrylnaphthalen-2-ol derivatives has not been reported. This, together with the mild conditions and operational simplicity, prompted us to examine this new homodimerization methodology in more detail.…”
Section: Resultsmentioning
confidence: 87%
“…Recently, we have reported several DDQ-mediated DHDA reactions from prenyl derivatives via in situ generated diene intermediates. ,, With our continued interest in exploring efficient cycloaddition reactions and oxidative dehydrogenations, we envisioned that the DDDA reaction would be realized by combination of our previously reported DHDA strategy with a metal-catalyzed dehydrogenative generation of dienophile. Among the metal-catalyzed dehydrogenative strategies, copper-catalyzed dehydrogenations have exhibited their powerful ability to convert alkanes to alkenes .…”
mentioning
confidence: 99%
“…These results further confirm the role of the intramolecular hydrogen bonding. Based on the experimental and calculation results and the previous literature, , a reasonable mechanism was proposed in Scheme . First, substrate 1a was oxidized by DDQ to form a carbocation intermediate via a dearomatization pathway.…”
mentioning
confidence: 99%